Zoneamento geoambiental do município de Casa Branca (SP) - Amaral, Ana Maria Carrascosa do [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Geoenvironmental studies, although recent, are increasingly gaining importance as a an environmental planning tool. The geoenvironmental zoning allows the determination of the potential and limitations of natural resources use, which facilitates a better use of the area, seeking their sustainability. Geo-environmental zones are defined by sectorial and/or integrated surveys of natural resources, using techniques of remote sensing and geoprocessing. This project has as main objective the development of a geo-environmental zoning in Casa Branca, state of São Paulo, at scale of 1:50.000, considering physiographic, geological/geotechnical and use and occupancy of land criteria, including location of Permanent Preservation Areas (PPA). The city suffers from problems related to lack of urban planning, seeing that there are many gullies in the region. The methodological steps of the zoning include: physiographic subdivision of the area, the mapping of land cover and use, the location of PPA's, fieldwork, and lastly, the integration of information obtained. After the execution of all project stages, the map of geo-environmental zoning of study area was obtained, from which interpretations were made for each unit about susceptibility for physical processes occurrence (mass movement, erosion, siltation and flooding) aiming to assist in planning and decisions about environmental issues, and also to provide a database for future environmental research in the area. As a result, were defined 4 Geoenvironmental Units, with emphasis on Unit D, by the high level of susceptibility for physical processes occurrence, mainly linear erosion, are therefore restricted areas for urban occupation. However, the city is within this unit, which indicates the need for planning for urban expansion in the city, so that erosion problems are avoided or minimized

Os estudos geoambientais, embora recentes, ganham cada vez mais espaço como uma importante ferramenta do planejamento ambiental. O zoneamento possibilita a determinação dos potenciais e limitações de uso dos recursos naturais, o que facilita um melhor aproveitamento da área, visando a sua sustentabilidade. As zonas geoambientais são definidas por meio de levantamentos setoriais e/ou integrados dos recursos naturais e do meio ambiente, com a utilização de técnicas de sensoriamento remoto e de geoprocessamento. A pesquisa tem como principal objetivo elaborar a carta de zoneamento geoambiental do município de Casa Branca (SP), na escala 1:50.000, considerando critérios fisiográficos, geológico-geotécnicos e de uso e ocupação da terra, incluindo a localização das Áreas de Preservação Permanente (APPs). O município sofre com problemas relacionados à falta de planejamento urbano, visto que existem muitas voçorocas na região. As etapas metodológicas do zoneamento incluem: a compartimentação fisiográfica, o mapeamento do uso e cobertura da terra, localização das APPs, trabalhos de campo e, por fim, a integração das informações obtidas. Após a execução de todas as etapas, obteve-se uma carta de zoneamento geoambiental, a partir da qual foram feitas interpretações, para cada unidade, acerca da suscetibilidade à ocorrência de processos do meio físico (movimentos de massa, erosão, assoreamento e inundação), com o intuito de auxiliar no planejamento e nas decisões relacionadas às questões ambientais, assim como disponibilizar uma base de dados para futuras pesquisas ambientais na região. Como resultado, foram definidas 4 Unidades Geoambientais, com destaque para unidade D, pelo alto grau de suscetibilidade para a ocorrência de processos do meio físico, principalmente erosão linear, sendo, portanto, áreas restritas para a ocupação urbana. No entanto, a cidade está inserida dentro desta unidade, o que...
Keywords: Engineering geology; Geologia de engenharia; Política ambiental; Planejamento urbano; Geoprocessamento; Zoneamento; Geologia ambiental; Casa Branca (SP)